PEMBUATAN MEDIA PEMBELAJARAN ANIMASI BILINGUAL DENGAN MENGGUNAKAN SOFTWARE MACROMEDIA FLASH 8 UNTUK BAB FLUIDA SMA KELAS XI SEMESTER GENAP - Wijaya, Rani (Scientia: Jurnal Hasil Penelitian, 2016)
One of the causes of Physics is less desirable, in the material of physics there are many concepts that are abstract so difficult to imagine. Therefore, many students simply work with physical formulas, without trying to learn the background of the underlying philosophy. One method of physics teaching is the use of Macromedia Flash 8 animation. This program is one of the computer program that can be used in developing the making of learning media. This research tries to explore how to make animation material bilingual fluid in SMA using Macromedia Flash 8. Based on data analysis in this study can be made a conclusion as follows: "By using the Macromedia Flash 8 animation program can be made learning media on temperature and caloric materials will be run with a computer that allows users to interact with the program." With this media the role of teachers is still large in the learning process because as a manager of teaching and learning activities in the classroom.